Real-time observation of a single DNA digestion by λ exonuclease under a fluorescence microscope field - Matsuura, Shun-ichi (Oxford University Press, 2001)
A fluorescence microscopy technique has been developed to visualize the behavior of individual DNA and protein molecules. Real-time direct observation of a single DNA molecule can be used to investigate the dynamics of DNA–protein interactions, such as the DNA digestion reaction by λ exonuclease. In conventional methods it is impossible to analyze the dynamics of an individual λ exonuclease molecule on a DNA because they can only observe the average behavior of a number of exonuclease molecules. Observation of a single molecule, on the other hand, can reveal processivity and binding rate of an individual exonuclease molecule. To evaluate the dynamics of λ exonuclease, a stained λ DNA molecule with one biotinylated terminal was fixed on an avidin-coated coverslip and straightened using a d.c. electric field. Microscopic observation of digestion of a straightened DNA molecule by λ exonuclease revealed that the DNA digestion rate was ∼1000 bases/s and also demonstrated high processivity.